2003
DOI: 10.6028/nist.ir.6948
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting ultrasonic extraction of lead from household paint films:

Abstract: Previous studies at NIST on the use of ultrasonic extraction/anodic stripping voltammetry (UE/ASV) for determining lead in household paint found that the particle size of the ground specimen plays an important role in lead extraction efficiency, particularly when the extraction is performed under the commonly used sonication conditions of 45 °C and 30 min. Consequently, it was proposed that, in conducting an UE/ASV analysis of a paint-film specimen in the field, the specimen particle size should be estimated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…The finding that after sonication of the field specimens essentially all the lead was found by NLLAP ICP analysis to be in the UE extract (Section 2.3.2.1) indicated that the sonicator operation conditions were successful in extracting lead from these specimens. Successful sonicator extraction of lead in field-sampled dust, which has generally small particle size (sub-millimeter range), was consistent with the results of previous NIST research on UE/ASV analysis of lead-containing paints [12,17]. In those studies, lead in paint specimens was successfully extracted by sonication at temperatures and times similar to those used in the present study provided that the paint specimens were ground sufficiently small (i.e., generally < 425 µm particle size).…”
Section: Results Analysis and Discussion 31 Laboratory-prepared Spsupporting
confidence: 86%
“…The finding that after sonication of the field specimens essentially all the lead was found by NLLAP ICP analysis to be in the UE extract (Section 2.3.2.1) indicated that the sonicator operation conditions were successful in extracting lead from these specimens. Successful sonicator extraction of lead in field-sampled dust, which has generally small particle size (sub-millimeter range), was consistent with the results of previous NIST research on UE/ASV analysis of lead-containing paints [12,17]. In those studies, lead in paint specimens was successfully extracted by sonication at temperatures and times similar to those used in the present study provided that the paint specimens were ground sufficiently small (i.e., generally < 425 µm particle size).…”
Section: Results Analysis and Discussion 31 Laboratory-prepared Spsupporting
confidence: 86%
“…Factory calibration of the ASV instrument was checked in the previous NIST UE/ASV paint studies [11][12][13]. A repeat calibration check performed at the beginning of the current study using six standardized lead nitrate solutions (7.5 % volume fraction nitric acid with lead contents ranging from 1 mg/L to 28 mg/L) confirmed that the instrument has remained in calibration.…”
Section: Experimental Designmentioning
confidence: 62%
“…One deviation from the apparatus instructions was that the extraction was performed with warm tap water (≈ 45 °C) in the sonicator bath. Use of warm water was based on the results of previous NIST studies showing that lead recovery from laboratory-prepared paint film specimens was enhanced at higher bath temperatures [12,13]. Another deviation was that, for half of the specimens tested by an operator, the extract solutions were filtered using a Millipore PTFE 0.45 mm filter.…”
Section: Ue/asv Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed studies of the sample processing conditions also suggest that particle size, sonication temperature and sonication time can strongly affect the UE/ASV extraction efficiency. 14 In this study, several common solvents (principally N-methylpyrrolidone) were examined as a way to prepare paint samples without the use of mechanical grinding, high-temperature digestion, or sonication. The physical properties of N-methylpyrrolidone (NMP) are well-suited to the eld analysis of paints.…”
Section: Introductionmentioning
confidence: 99%